Investigating Influential Factors in Scarlet Product Purchases through Global Marketing insights: Menyelidiki Faktor-Faktor yang Berpengaruh dalam Pembelian Produk Scarlet melalui wawasan Pemasaran Global - Nurhasanah, Zenith; Indayani, Lilik (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the determinants influencing the purchasing decisions of scarlet skincare and bodycare products among users in Sidoarjo City, Indonesia. Utilizing a quantitative approach, data was collected from 100 respondents through online questionnaires. The findings reveal that product quality, brand image, and promotional activities significantly impact purchasing decisions, with product quality being the most influential factor, followed by brand image and promotional strategies. These insights provide valuable guidance for scarlet product manufacturers and marketers to tailor their strategies effectively, ultimately enhancing customer satisfaction and brand loyalty in the competitive skincare and bodycare market. Highlights: 1. Investigates factors influencing scarlet product purchases.2. Product quality, brand image, and promotions significantly affect decisions.3. Insights aid scarlet product marketers in enhancing brand loyalty. Keywords: Scarlet products, purchasing decisions, skincare, brand image, promotional strategies.